2010
DOI: 10.1007/s10750-010-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypoxia and organic enrichment on estuarine macrofauna in the inner part of Ariake Bay

Abstract: In the inner part of Ariake Bay, Japan, hypoxia frequently occurs in summer at the organically enriched bottom with salinity stratification caused by flooding after the rainy season. Sediment organic enrichment can work as a stressor for macrobenthos. To investigate the effects of both hypoxia and sediment organic enrichment on macrobenthos, samples were collected at 20 stations by grab sampling in May and August, representing the situation before and after hypoxia, respectively. Although sediment grain size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
16
1
Order By: Relevance
“…As the severity of hypoxia differs depending on the year, not all summer hypoxic events cause drastic changes in benthic communities. However, occasional severe hypoxia causes mass mortality of macrobenthos (Yoshino et al 2010). Hypoxia would surely contribute to the disappearance of other large species from the benthic community in the present study area over a long period.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…As the severity of hypoxia differs depending on the year, not all summer hypoxic events cause drastic changes in benthic communities. However, occasional severe hypoxia causes mass mortality of macrobenthos (Yoshino et al 2010). Hypoxia would surely contribute to the disappearance of other large species from the benthic community in the present study area over a long period.…”
Section: Discussionmentioning
confidence: 76%
“…Benthic communities are devastated during years of severe hypoxia, as observed in 2006 (Yoshino et al 2010). Small short-lived species can quickly recover during years of moderate hypoxia, which partly explains why small species dominate in hypoxia-stressed sites in general.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…damming, use of fertilizers, urban effluents) . Moreover, in semi-enclosed bays the reduced exchange with the open sea promotes water stagnation and reinforces hypoxic conditions (Yoshino et al, 2010) which may result in total absence of oxygen (i.e. anoxia).…”
mentioning
confidence: 99%
“…These results indicate that the rapid decline in the macro-benthic communities was not simply caused by the progress of organic enrichment of the sediment with the development of reduced conditions, but occurred even in the oxidic sediment with much less oxygen consumption of the overlying water. Yoshino et al (2010) examined the distribution of the macro-benthic communities and the major environmental factors that controlled their distributions in the inner part of Ariake Bay, and found that the changes in the structure of the macro-benthic communities were not caused by stress as a result of the increased TOC content of the sediment, but that they mainly arose from physiological stress caused by the occurrence of hypoxic water. Our results suggest a possibility that the transportation of hypoxic water by the tidal currents may explain these phenomena, since Ariake Bay has the largest tidal amplitude (over 6 m at the spring tide) on the Japanese coast, and it often generates a fast tidal current along the longitudinal axis of the bay (Inoue 1980, Odamaki et al 2003.…”
Section: Progress Of Organic Enrichment Of the Sedimentmentioning
confidence: 99%